A Digital Diagnosis Tool for Children with Dyslexia against Similar Criteria DSM-5 - Bazuhair, Narjees Abdulghaffar; Bazuhair, Naseem Abdulghaffar (Journal of Intellectual Disability - Diagnosis and Treatment, 2023)
Background: we stand on the fact that what makes diagnosing dyslexia difficult is that students with dyslexia are of very normal or even extraordinary intelligence. It is important to prepare a tool that enables the initial diagnosis of this disorder, and in the light of its results, a report is formulated on the degree of injury of the person being tested. Aims: The aim is to develop a reliable and validated tool for children with dyslexia. Methods: A convenience sampling method was used to select children aged 4-8 years as the study population. Inclusion criteria were (1) age between 4 and 8 years; (2) be able to speak; and (3) Keep attending kindergarten and school. Children’s parents and teachers were given full information about the study, and all signed an informed written consent form. Ninety children were included in this study. Word spelling Test, Letter rapid automatized naming Test, Recognition of a first sound test, Deletion of a first sound test, Blending test, and Segmentation test was developed and used. Findings: The content validity of all tests was measured. The correlation coefficients between each subscale and the total scale ranged from 0.54 to 0.58. Conclusion: This tool is expected to assist teachers in identifying, accurately assessing, and formulating a learning program that fits the abilities and needs of the children.